2016
DOI: 10.1007/s00220-016-2614-y
|View full text |Cite
|
Sign up to set email alerts
|

Herman’s Condition and Siegel Disks of Bi-Critical Polynomials

Abstract: Abstract. We extend a theorem of Herman from the case of unicritical polynomials to the case of polynomials with two finite critical values. This theorem states that Siegel disks of such polynomials, under a diophantine condition (called Herman's condition) on the rotation number, must have a critical point on their boundaries.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…If c has a higher multiplicity, the symmetry arguments are more involved: we refer to [CR,Proposition 26 and Paragraph 4.11.6] for the proof of the fact that ∆ = ∆. Now, as in the proof of Proposition A, the complement of ∆ can be uniformized to C \ D via a holomorphic map Φ, in order to get, by Schwarz reflection, an analytic map g defined in a neighborhood of S 1 , such that g| S 1 is an analytic circle map with no critical points (see [CR,Lemma 30]). As g is conjugate to f in a small neighborhood of the unit disk, using the fact that f : U → V has degree d, it can be shown that also g has degree exactly d on S 1 [CR,Lemma 30].…”
Section: Proof Of Proposition Cmentioning
confidence: 99%
See 3 more Smart Citations
“…If c has a higher multiplicity, the symmetry arguments are more involved: we refer to [CR,Proposition 26 and Paragraph 4.11.6] for the proof of the fact that ∆ = ∆. Now, as in the proof of Proposition A, the complement of ∆ can be uniformized to C \ D via a holomorphic map Φ, in order to get, by Schwarz reflection, an analytic map g defined in a neighborhood of S 1 , such that g| S 1 is an analytic circle map with no critical points (see [CR,Lemma 30]). As g is conjugate to f in a small neighborhood of the unit disk, using the fact that f : U → V has degree d, it can be shown that also g has degree exactly d on S 1 [CR,Lemma 30].…”
Section: Proof Of Proposition Cmentioning
confidence: 99%
“…They will only be used in the proof of Proposition C, in Section 4. Most of them can be found or deduced from results in [CR,section 2], but we include the proof here for completeness and self-containment. PROPOSITION 2•6.…”
Section: •3 Properties Of Hatsmentioning
confidence: 99%
See 2 more Smart Citations
“…Now we investigate the case, in which W is a Siegel disk and its boundary ∂W is a Jordan curve. Several cases in which this occurs and ∂W contains a critical point, are listed and studied in [18], [24], and [7]. One such case is presented in the Main Theorem of [24].…”
Section: From Proposition 23 Of [12]mentioning
confidence: 99%